The Effect of Video in Teaching Writing Skill across Different Personality: Pengaruh Video dalam Mengajarkan Keterampilan Menulis di Berbagai Kepribadian - Faridha, Noor (Universitas Muhammadiyah Sidoarjo, 2019)
This research aims to investigate: firstly, whether there is the effect of videos as the authentic materials on the student’s achievement writing recount paragraph between two groups. Secondly, conducted to know whether there is different in the achievement writing recount paragraph of students’ introvert and extrovert and the thirdly, the basic interaction form of learning tough using video and students personality in writing recount paragraph. This study uses quasi-experimental research design. The population of the research was the eighth grade students of PLUS ISYHAR Junior High. The students of class 8-1 consist of 30 students as the experimental group, and the students of class 8-3 consist of 32 students as the control group. The result of the research showed several results. First, there is significant difference in the students’ writing recount paragraph taught by using video as the authentic materials and conventional technique. Second, the result of the research showed that extrovert and introvert students’ had the same result of writing paragraph recount. Third, there is no interaction between students taught using video and students’ personality in writing recount paragraph.